Evaluating Auditor Attributes: Implications for Audit Quality: Pengaruh Kompetensi, Independensi, dan Etika terhadap Kualitas Audit: Studi Kuantitatif - Abdul Muiz Muzaqi; Eny Maryanti (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative research aims to investigate the influence of competence, auditor independence, and ethical behavior on audit quality within the context of the Inspectorate Office in Sidoarjo Regency. Using a full sampling approach due to the relatively small population of 50 employees, the study employed SPSS V.25 for statistical analysis. The results reveal that competence, independence, and ethics significantly affect audit quality at the Inspectorate Office in Sidoarjo. This study underscores the critical role of these factors in enhancing the quality of audits, with implications for audit practitioners and regulators globally, emphasizing the importance of competence, independence, and ethics in maintaining the integrity of audit processes. Highlights: Competence, independence, and ethics influence audit quality. Quantitative research conducted at Inspectorate Office in Sidoarjo. Implications for audit integrity and regulatory considerations. Keywords: Audit Quality, Competence, Independence, Ethics, Inspectorate Office.